Analysis of Oil and Gas Exports Imports on the Indonesian Rupiah Exchange Rate in 1980-2020 - Murtaza Hussain; Rully Firmansyah; Firsty Ramadhona Amalia Lubis; Lusmino Basia (Journal of Asset Management and Public Economy (JAMPE), 2023)
International trade is important activities for the economy. The advantages and benefits in international trade that can be obtained by a country is that it allows the opportunity to specialize in obtaining goods and services at lower prices. Therefore, the contribution of this study is to analyze exports, imports, inflation, and economic growth against the Indonesian rupiah exchange rate. The dependent variable used is the rupiah exchange rate variable, and the independent variables include oil and gas exports, oil and gas imports, inflation, and economic growth. Data that used is secondary data obtained through the official website of the World Bank, and the Central Statistics Agency (BPS). The method used is the Multiple Linear Regression model. Based on the results of the regression calculations show that the variable oil and gas exports have no significant effect, oil and gas imports have a positive and significant, inflation has no significant effect, and economic growth negative and significant effect on the rupiah exchange rate.